(untitled) (Journal of Enam Medical College, 2012)
Background: The pattern of skin diseases varies from one country to another and even from region to region of the same country. We are geographically placed in the tropical region with natural outcome of communicable diseases. We conducted this cross sectional study in a tertiary hospital of Bangladesh keeping the proposition in mind that infectious diseases occupy maximum percentage among skin and venereal diseases in outpatients in Bangladesh. Objectives: To classify the diseases attending the Skin & VD outpatient department of Enam Medical College Hospital (EMCH) and to draw comments and recommendations on the basis of findings. Materials and Methods: All patients irrespective of age and sex attending the OPD of Skin-VD Department of Enam Medical College Hospital during a 2-year time-period (from January 2009 to December 2010) were included in the study. Structured questionnaire, check-list and face-to-face interview (whenever necessary) were used as tools of data collection. Statistical analyses were done by SPSS version Windows 11.1. Results: Total number of patients was 12100. Most of the patients were aged (>18 years; 64.28%), dominated by male (61.63%), married (56.1%), literate (71.11%), coming from far (>5 km; 63.5%) and of middle class origin (59.73%). Out of the total cases, maximum (23.42%) were diagnosed as eczema, followed by infectious diseases (17%), acne (8.69%) and psoriasis (6.36%). Conclusion: In this study we found infectious diseases to occupy the second position next to eczema and our findings nullify the proposition that infectious diseases occupy maximum percentage among skin and venereal diseases in outpatients in Bangladesh. DOI: http://dx.doi.org/10.3329/jemc.v1i2.11465 J Enam Med Col 2011; 1(2): 67-70